Nutritional Management of a Patient with ESRD and AMI: A Case Study on Energi-Protein Adequacy and Clinical Improvement - Pertiwi, Zahwa Hana; Prihatin, Setyo; Yuniarti, Yuniarti (JGK: Jurnal Gizi dan Kesehatan, 2025)
Background: Chronic kidney disease is a major risk factor for cardiovascular disease, and the risk increases as kidney function declines. Objective: To present a case study of a patient with ESRD and AMI, focusing on clinical conditions and energy–protein adequacy through nutritional care. Methods: An observational case study in a hospital setting, with data collected through interviews, observation, and medical records. Results: Over five days of nutritional intervention, energy intake increased from 62% to 88% of requirements, and protein from 54% to 105%. Clinical improvements included reduced nausea and better food tolerance. Conclusions: Stepwise nutritional interventions, from liquid to regular diet, improved energy–protein intake and supported clinical recovery in an ESRD patient with AMI.